(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Introduction Writing, one of the four essential macro-skills in language learning, is pivotal in the educational framework. It is interwoven with the other three skills—reading, listening, and speaking—and cannot be acquired in isolation. A critical factor in developing writing proficiency lies in the language of instruction. This is particularly evident in regions where the language spoken at home differs from that used in formal education. In such cases, learners are more exposed to their native language or mother tongue, significantly supporting their literacy journey. While it is true that the Filipino language is introduced to students as early as Grade 1, its use is often confined to the Filipino subject. This limited exposure can hinder the students’ writing skills as they need more practice utilizing Filipino as a medium of instruction. Students often gravitate towards using their mother tongue even when attempting to write basic phrases and sentences, leading to numerous errors. Consequently, Filipino and English competency tends to center more on oracy and rudimentary language skills during the initial stages. A pivotal juncture in the transition of instruction typically occurs around Grade 4. This phase calls for bridging the gap between the student’s first language (L1) and the second language (L2) instruction, which is essential for achieving the critical standards of the curriculum, such as effective communication through the medium of instruction and the development of higher-order thinking skills in writing composition. Such an instructional shift is particularly felt in educational institutions like the researcher’s current assignment at the Ilocanos Elementary School. Although the City of San Fernando, La Union, where the school is situated, is considered a cultural melting pot with robust usage of the Filipino language, public school learners have transitioned back to using the Ilokano language as their primary mode of instruction for the past four years. This shift becomes a significant context as Grade 4 learners, coming from this environment, enter the stage with foundational competencies in both Filipino and English. Against this backdrop, the present study aimed to evaluate the Filipino writing competence of Grade 4 learners at Ilocanos Elementary School. This assessment sought to serve as the basis for creating a supplementary writing guide tailored to Grade 4 students. Method To this end, a descriptive research design was employed to gauge the level of writing competence in terms of mechanics, grammar, organization, and content. Students’ written samples were examined for each topic to derive insights. The study’s locale was Ilocanos Elementary School, and the sample of Grade 4 learners was chosen through purposive sampling. Inclusion criteria encompassed learners transitioning from mother tongue to bilingual instruction, enrolled in the school, and belonging to the designated grade level section. Upon analyzing the data using descriptive and inferential statistics, the study delineated the respondents’ writing competence in using the Filipino language. This competency was further categorized into mechanics, grammar, organization, and content. Results and Discussion The respondents’ overall competence yielded a weighted mean of 2.91, suggesting a moderately competent level of writing. Examining the mechanical aspects of writing, the study identified areas of concern, including punctuation marks, capitalization, and syllabication. The findings underscored the respondents’ moderate competence (3.22) in using these elements. Among the mechanical components, orthography and capitalization of Filipino words were particularly challenging, receiving mean ratings of 3.04 and 3.06, respectively. Moving on to grammar, the learners’ competency was rated at 3.36, indicating a moderately competent level. The study highlighted two areas of concern: compositional violations involving run-on sentences and the use of function words. The organization was also assessed as a writing skill, revealing a moderately competent level (2.97). This implies that the student’s confidence in structuring their thoughts during written expression requires further development. Regarding content, the respondents’ competence was rated as moderately competent, with a weighted mean score of 2.97. Overall, the study indicated that while the students had achieved a certain level of competence in these various aspects of writing, they still felt the need for guidance from teachers or knowledgeable individuals. Based on the identified competencies and areas for improvement, the researcher developed a supplementary writing guide tailored to Grade 4 learners. This guide aimed to provide self-assistance in nurturing writing competence in the Filipino language. Conclusion The study delved into the intricacies of Grade 4 learners’ Filipino writing competence, unveiling a nuanced picture of their proficiency in mechanics, grammar, organization, and content. This exploration highlighted the complex interplay between language instruction, home language exposure, and learners’ challenges in transitioning between languages. The development of the supplementary writing guide underscores a proactive approach to enhancing students’ writing abilities and bridging the gaps in their communicative competence. As education continues to evolve, future investigations into various dimensions of Filipino language competence are strongly advocated, seeking to unravel the intricacies of language acquisition and its profound impact on holistic learning.